Analisis Semiotika Perbandingan Antara Logo Halal MUI Dengan Logo Halal Baru - Maysya Tri Putri; Jamiati KN; Daniel Handok (Journal on Education, 2023)
The message being conveyed can have many meanings depending on the perspective of the recipient of the message. This tempts the author to raise the topic of this presentation on the semiotic analysis of the Halal logo as a communication with its own uniqueness. Messages that are compatible with the vision, mission, soul and personality of the institution, as well as the halal logo, are considered elements included in the logo. Authors refer to journal articles, books and presentation materials using Pierce's method of semiotic analysis. The purpose of this study is to provide a semiotic analysis of the Indonesian halal logo published by the Halal Product Guarantee Agency of the Republic of Indonesia (BPJPH). As well as knowing the comparison between the logos issued earlier and the latest.